Contributions of Skinner's theory of verbal behaviour to language interventions for children with autism spectrum disorders. Issue 3 (3rd April 2017) - Johnson, Gaige; Kohler, Kelly; Ross, Denise
ABSTRACT: The purpose of the current paper is to describe the impact of applied behaviour analysis on language treatment for children with autism spectrum disorders (ASDs) diagnoses. Specifically, this paper will describe Skinner's theory of verbal behaviour and its contributions to evidence-based treatments for communication deficits among individuals with ASD. Skinner's book Verbal behavior was written in 1957 but saw increased growth in research publications after its application to individuals with autism in the 1990s. Today, verbal behaviour is an accepted evidence-based practice in behaviour analysis, and mastery of Skinner's theory of verbal behaviour is required for practising behaviour analysts who teach individuals with autism. This paper describes the history of the theory of verbal behaviour, defines the key features of the theory, and presents research supporting its application to the communication development of children with autism.